An evaluation of the benefits and challenges of video consulting between general practitioners and residential aged care facilities. (December 2015) - Wade, Victoria; Whittaker, Frank; Hamlyn, Jeremy
This research evaluated a project that provided video consultations between general practitioners (GPs) and residential aged care facilities (RACFs), with the aim of enabling faster access to medical care and avoidance of unnecessary hospital transfers. GPs were paid for video consultations at a rate equivalent to existing insurance reimbursement for supporting telehealth services. Evaluation data were gathered by direct observation at the project sites, semi-structured interviews and video call data from the technical network. Three pairs of general practices and RACFs were recruited to the project. 40 video consultations eligible for payment occurred over a 6 month period, three of which were judged to have avoided hospital attendance. The process development and change management aspects of the project required substantially more effort than was anticipated. This was due to problems with RACF technical infrastructure, the need for repeated training and awareness raising in RACFs, the challenge of establishing new clinical procedures, the short length of the project and broader difficulties in the relationships between GPs and RACFs. Video consulting between GPs and RACFs was clinically useful and avoided hospital attendance on a small scale, but further focus on process development is needed to embed this as a routine method of service delivery.